Evidence for a Structural Analysis of Target Selection in Picture Viewing (Journal of Eye Movement Research, 2011)
Spontaneous fixations onto shapes are driven by a structural analysis. But is such analysis also carried out during free viewing of real-world scenes? Here, we analyze how fixation locations in such scenes are related to their region using the region's symmetric axes as a reference. Each fixation location is compared with respect to its nearest symmetric-axis segment by a latitude and a longitude measure. Analyzing the distributions for the two measures we find that there exist fixation biases for L features and parallel contours, suggesting that structural analysis may play a role in saccadic target selection during free viewing.